Efektivitas Kuliah Kerja Nyata Kelompok 146 dalam Meningkatkan Keterampilan Sosial Mahasiswa Universitas Islam Negeri Sumatera Utara di Desa Paya Perupuk - Muniruddin Muniruddin; Uswatun Hasanah Lubis; Muhammad Arif; Hafizah Ismayati (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Real Work Lectures (KKN) are an integral part of the higher education curriculum in Indonesia which are designed to provide practical experience to students in the field. This research aims to evaluate the effectiveness of KKN carried out by Group 146 in improving the social skills of students in Paya Perupuk Village. This research approach is qualitative using observation, interview and questionnaire methods. The research results show that this KKN program has succeeded in improving students' social skills, especially in terms of communication, teamwork and adaptability in the community environment.